2018
DOI: 10.1380/ejssnt.2018.396
|View full text |Cite
|
Sign up to set email alerts
|

HAXPES Study on the Chemical States of Reaction Films Formed on Metal Surfaces by Zinc Dialkyl Dithiophosphate

Abstract: The fuel-saving performance of automotive lubricants greatly depends on the composition and structure of the reaction films that form on metal surfaces through chemical reactions between the additives in the lubricant and the metals. In this study, we prepared reaction films on metal surfaces using two lubricants formulated with different base oils of different degrees of polarity and an anti-wear additive commonly used in automotive engine oils, and examined the chemical state of the films using HAXPES. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Therefore, lubricants are being developed to reduce the friction losses in these systems. Lubricants can be categorized as solid lubricants [2][3][4], semisolid lubricants [5], and liquid lubricants [6][7][8]. Liquid lubricants under boundary lubrication reduce friction and wear by forming an adsorption and reaction layer at the friction interface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lubricants are being developed to reduce the friction losses in these systems. Lubricants can be categorized as solid lubricants [2][3][4], semisolid lubricants [5], and liquid lubricants [6][7][8]. Liquid lubricants under boundary lubrication reduce friction and wear by forming an adsorption and reaction layer at the friction interface.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we utilized X-ray photoemission spectroscopy (HAXPES) to examine the chain lengths of polyphosphates in the reaction films formed by ZnDTPs (zinc dialkyl dithiophosphate, a common anti-wear additive in automotive engine oils) having either shorter or longer alkyl groups [1][2][3][4][5] as part of a mechanistic study on the formation of reaction films. We found that the length of the alkyl groups in ZnDTPs affected the chain lengths of the polyphosphates in the reaction films [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%